Uma análise do agir linguageiro de licenciandos cotistas no PIBID/Letras – Inglês - Morais, Daniel Sousa (2017)
This Master thesis aims to investigate the language action about the teaching work of English Language and Literature degree students, who got into the college through quotas and take part of the subproject PIBID, as well as it aims to investigate how the action reveals the real work and the teaching identity constitution. Therefore, it is a qualitative research, of interpretative paradigm, and focuses on data, which were generated in two English classes in Elementary School, under the activities developed in the subproject called PIBID/Letras - Inglês of Federal University of Paraíba, in 2015, through self-confrontation interviews. Situated in Applied Linguistics field, this study is grounded in the perspective of the social subject in the recent modernity (MOITA LOPES, 2002, 2006a, 2006b, 2013a, 2013b; HALL, 2015; BAUMAN, 2001; REICHMANN, 2012, 2015) as having a fragmented identity and as being in a constant (de)construction process. It is also grounded in the Sociodiscursive Interactionism theoretical-methodological frameworks (BRONCKART, [1999] 2012, 2006, 2008) and the notions of Work Sciences (CLOT, 2007[1999], 2010; NOUROUDINE, 2002; AMIGUES, 2004). Hence, it was identified the thematic contents which emerged in the texts/discourses produced by the research collaborators, namely: (i) Conflicts in the teaching context; (ii) Surprises in the teaching context; and (iii) Appropriation of the professional gender: being a teacher. Considering that the identity construction occurs socially and discursively, an analysis of the enunciative level of the texts/discourses has been done according to the SDI, taking into account, mainly, the voices and the modalizations that appeared in the collaborators speech. It was also identified the real work and its implications from the constructed representations. The voices, which were raised by the teachers in training, revealed how the pibidiano work collective, the prescriptions of the official documents and the students, play a central role in the identity constitution. In addition to the voice of the empirical author that is marked by the responsibility of these collaborators as teachers, the modalizations, which in turn demonstrate the collaborators comments and evaluations about the teaching exercise, their conceptions, which was acquired throughout their lives and that, are fundamental to understand the assumption process as English teachers. It was also noticed that the collaborators, perceiving the distance between the accomplished work and the non-accomplished work, revealed several feelings about the teaching exercise, such as surprise, relief and annoyance, thus, promoting an reflection about the being teacher and the perception of themselves as teachers.